E0244 How low we should go in elderly patients with type 2 diabetes and hypertension in Chinese Han people. (17th November 2010) - Chen, Gang; Lai, Xiaolan; Lin, Lixiang
Abstract : Background: The benefits of lowering systolic blood pressure (SBP) below140 mm Hg in elderly patients with type 2 diabetes and hypertension are unclear. Methods: Elderly (age ≥65 years) patients with type 2 diabetes and hypertension underwent 12-lead ECG. The R-wave voltage in lead aVL (RaVL ≥0.57 mV) was used to assess CVD risk. GFR was estimated by Cockcroft-Gault formula. 235 patients were tight SBP controlled (130–139 mm Hg), and 472 patients were less tight SBP controlled (140–159 mm Hg). Results: The height of RaVL and risk of the height of RaVL ≥0.57 mV was no significance difference between the two groups, but some decline in eGFR was found in the less tight control group (adjusted mean 55.61 vs 59.65, p=0.06) although the decrease was not statistically significant. Conclusions: In elderly patients with type 2 diabetes and hypertension, to achieve the target SBP of below 140 mm Hg seems reasonable.